Translation and cross-cultural adaptation of the ICHOM standard set for stroke: the Dutch version - Daniëlla M Oosterveer; Winke van Meijeren-Pont; Frederike van Markus-Doornbosch; Etienne Stegeman; Caroline B Terwee; Gerard M Ribbers; Thea PM Vliet Vlieland (SpringerOpen, 2023)
Abstract Introduction The International Consortium for Health Outcomes Measurement (ICHOM) developed a standard set of patient-centered outcome measures for use in stroke patients. In addition to the Patient-Reported Outcomes Measurement Information System (PROMIS) Global Health, it is comprised of 25 questions that are not part of a specific questionnaire. This study aimed to translate these 25 single questions into Dutch. Methods Two native Dutch-speaking translators independently translated the original ICHOM questions into Dutch. A consensus translation was made by these translators and a third person. This translation was subsequently translated back to English independently by two native English-speaking translators. Afterwards a pre-final version was made by consensus of a committee. After field-testing among 30 stroke patients, a final version was made. Results The forward and backward translations led to eight cross-cultural adaptations. Based on the interviews with stroke patients, 12 questions were changed to enhance comprehensibility leading to a final Dutch translation of the 25 single questions. Conclusions A Dutch translation of the 25 single questions of the ICHOM Standard Set for Stroke was developed. Now a complete ICHOM Standard Set for Stroke can be used in Dutch populations allowing comparison and improvement of stroke care.